Class I hysterectomy in stage Ia2-Ib1 cervical cancer - Chen, Long (Wideochir Inne Tech Maloinwazyjne, 2018)
INTRODUCTION: During the last 3 decades, the standard treatment for stage Ia2-Ib1 cervical cancer has been Piver-Rutledge class II or III radical hysterectomy. However, this surgery is associated with a high rate of urologic morbidity. AIM: To determine the efficacy of class I radical hysterectomy compared with class III radical hysterectomy in terms of morbidity, overall survival, and patterns of relapse in patients with Ia2-Ib1 cervical cancer undergoing primary surgery. MATERIAL AND METHODS: A total of 101 patients with stage Ia2-Ib1 cervical cancer < 2 cm were randomized to class I and class III hysterectomy groups. Clinical, pathologic, and follow-up data were prospectively collected. Univariate analysis was carried out. Of the total patients, 45 were randomized to class I surgery and 56 to class III surgery. No significant differences were observed in terms of pathologic findings or adjuvant treatment (p > 0.05). The morbidity rates were higher after class III surgery. RESULTS: The difference in recurrence rate between the class I and class III groups was not statistically significant (p > 0.05). The 5-year overall survival rate was 93% and 91%, respectively (p > 0.05). There were no significant differences in terms of recurrence rate or overall survival among patients with stage Ia2-Ib1 cervical cancer < 2 cm who underwent class I or radical (class III) hysterectomy. Morbidity was proportional to the extent of radicality. CONCLUSIONS: These data confirm the need for reducing surgical radicality in the treatment of patients with early cervical cancer, by tailoring the extent of resection according to the extent of disease.